The effect of firm size and profitability on firm value with capital structure as intervening variables in Indonesia / Indra Arifin Djashan - Djashan, Indra Arifin (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
This study examines the impact of firm size and profitability on firm value with capital structure as an intervening variable in financial companies listed on the Indonesia Stock Exchange during three years. The method used for sampling is purposive sampling based on predetermined criteria. The number of samples in this study were 73 companies. Measurement of profitability is using ROA and ROE as one indicator to see company performance. The main purpose of companies that have gone public is to increase the prosperity of the owners or shareholders through increasing the value of the company. The results showed that the improvement of profitability and firm size may improve its capital structure. The improvement of profitability and the firm size may increase significantly the firm value. The results of mediating test showed that the capital structure is not able to mediate the relationship between the profitability and firm size to firm value.